2
$\begingroup$

I have the following series

$$\sum_{k=1}^\infty \frac{(k-1)!}{(k+N)!},\quad\text{where }N \in \mathbb{N}. $$

I have found out that the series is equal to

$$\sum_{k=1}^\infty \biggl(\frac{1}{k}\cdot \frac{1}{k+1}\cdot _{...} \cdot \frac{1}{k+N}\biggr)$$

I also know that for $N=1$ we can use partial fraction expansion and we get a telescoping sum of $1 + \frac{1}{2} - \frac{1}{2} + \frac{1}{3} - \frac{1}{3} + ... + \frac{1}{k+1}$ which leaves $1$ if $k$ is heading to $\infty$.

Does anyone have any idea how I can go about doing this ?

$\endgroup$
5
$\begingroup$

To avoid a division by $0$, you should really start at $k=1$. Using @DanielFischer's hint, the telescoping goes as$$\begin{align}\sum_{k\ge1}\frac{1}{k\cdots(k+N)}&=\frac1N\sum_{k\ge1}\frac{k+N-k}{k\cdots(k+N)}\\&=\frac1N\sum_{k\ge1}\left(\frac{k+N}{k\cdots(k+N)}-\frac{k}{k\cdots(k+N)}\right)\\&=\frac1N\sum_{k\ge1}\left(\frac{1}{k\cdots(k+N-1)}-\frac{1}{(k+1)\cdots(k+N)}\right)\\&=\frac1N\left(\left.\frac{1}{k\cdots(k+N-1)}\right|_{k=1}-\lim_{k\to\infty}\frac{1}{k\cdots(k+N-1)}\right)\\&=\frac1N\left(\frac{1}{N!}-0\right)\\&=\frac{1}{N\cdot N!}.\end{align}$$

$\endgroup$
  • $\begingroup$ This is brilliant. But can you please explain how you got $N!$ at the end. $\endgroup$ – Zntzozt Dec 4 '19 at 22:38
  • $\begingroup$ @V1C10USG4M3R See edit. $\endgroup$ – J.G. Dec 4 '19 at 23:03
3
$\begingroup$

The neat thing about $p_n(x) =\prod_{k=0}^{n-1}(x+k) $ is that is telescopes in both numerator and denominator.

$\begin{array}\\ p_n(x+1)-p_n(x) &=\prod_{k=0}^{n-1}(x+1+k)-\prod_{k=0}^{n-1}(x+k)\\ &=\prod_{k=1}^{n}(x+k)-\prod_{k=0}^{n-1}(x+k)\\ &=(x+n)\prod_{k=1}^{n-1}(x+k)-x\prod_{k=1}^{n-1}(x+k)\\ &=((x+n)-x)\prod_{k=1}^{n-1}(x+k)\\ &=n\prod_{k=0}^{n-2}(x+1+k)\\ &=np_{n-1}(x+1)\\ \text{so}\\ \dfrac{p_n(x+1)-p_n(x)}{n} &=p_{n-1}(x+1)\\ \text{or}\\ \dfrac{p_{n+1}(x)-p_{n+1}(x-1)}{n+1} &=p_{n}(x)\\ \text{and}\\ \dfrac1{p_n(x)}-\dfrac1{p_n(x+1)} &=\dfrac1{\prod_{k=0}^{n-1}(x+k)}-\dfrac1{\prod_{k=0}^{n-1}(x+1+k)}\\ &=\dfrac1{\prod_{k=0}^{n-1}(x+k)}-\dfrac1{\prod_{k=1}^{n}(x+k)}\\ &=\dfrac{x+n}{\prod_{k=0}^{n}(x+k)}-\dfrac{x}{\prod_{k=0}^{n}(x+k)}\\ &=\dfrac{(x+n)-x}{\prod_{k=0}^{n}(x+k)}\\ &=\dfrac{n}{p_{n+1}(x)}\\ \text{so}\\ \dfrac1{n}\left(\dfrac1{p_n(x)}-\dfrac1{p_n(x+1)}\right) &=\dfrac{1}{p_{n+1}(x)}\\ \text{or}\\ \dfrac1{n-1}\left(\dfrac1{p_{n-1}(x)}-\dfrac1{p_{n-1}(x+1)}\right) &=\dfrac{1}{p_{n}(x)}\\ \end{array} $

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.